Application of the Quantum Teaching Learning Model to Improve Mathematics Learning Outcomes in Grade IV Students at SD Inpres 3 Tondo - Umul Khairah; Azizah Azizah; Khairunnisa Khairunnisa; Abdul Rahman; Sukri Sukri (Journal of Educational Sciences, 2026)
This research aims to improve the learning outcomes of mathematics students in grade IV of SD Inpres 3 Tondo through the application of the Quantum Teaching learning model. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles. Each cycle consists of the stages of planning, implementation of actions, observation, and reflection. The research subjects amounted to 34 grade IV students of SD Inpres 3 Tondo. Data collection techniques are carried out through tests, observations, and documentation. Data were analyzed using quantitative and qualitative analysis. The results of the study showed that there was an increase in students' mathematics learning outcomes in each cycle. In the pre-action stage, the average score of students was 45.74 with classical learning completeness of 5.9%. After the application of the Quantum Teaching model in cycle I, the average score increased to 71.76 with classical learning completeness of 67.65%. In cycle II, the average score increased again to 79.12 with classical learning completeness reaching 91.18%. These results show that the application of the Quantum Teaching learning model is able to improve the mathematics learning outcomes of grade IV students of SD Inpres 3 Tondo. Thus, the Quantum Teaching model can be one of the effective learning alternatives to improve the understanding and learning outcomes of mathematics in elementary school.